'Wong Ah Fook Museum' : proposed Wong Ah Fook Museum at Jalan Wong Ah Fook, Johor Bahru, Johor - 433051 Chan, Pau Moy (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2005